Le Corbusier’s Immeuble-villas and an after lunch remembrance - Sequeira, M. (II Congreso Internacional Cultura y Ciudad La Casa. Espacios domésticos, modos de habitar, 2019)
In November 1922 at the Urbanism Stand of the Autumn Salon in Paris, Le Corbusier presented, for the first time, the immeuble-villas project. It emerged as a new typology of collective housing, including private spaces –120 apartments– and communal areas – warehouse, central kitchen, restaurant, launderette, running track, solariums and sports, game, study and party facilities. In the first volume of his Œuvre Complète, Le Corbusier points out that Immeuble-villas was sketched «onto the back of a restaurant menu». However, a research at the Archives of the Le Corbusier Foundation uncovered a set of sketches in his personal diary, a unique finding that may have been one of the first trials about the Immeuble-villas project, or perhaps even the very first one. This set of sketches may help to illuminate some questions about this iconic project, which was never built but that plays even today an undeniably important role in architectural production worldwide.